Analisis Faktor Stress, Keteraturan Pola Makan dan Konsumsi Bahan Pangan Iritatif Terhadap Kejadian Dyspepsia - A. Dedi Rusmanto; Fara Nindya Maharani; Meddy Setiawan; Annisa Nurul Arofah (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Stress, regular diet, and consumption of irritating food are some of the risk factors for dyspepsia. Medical students at the first level undergo a fairly high density of activities, where this requires an adaptation process that can cause stress. In stressful conditions, the regularity of eating patterns is disrupted. There are also many incidents of students consuming irritating foodstuffs.Aims of researchto analyze stress factors, regularity of eating patterns and consumption of irritating foodstuffs onthe incidence of dyspepsia in first-year medical faculty students.This research is an analytic observational study with a cross sectional study approach. The research activity was carried out at UMM Medical Faculty in November 2019 involving 60 students of the 2019 class. The sampling technique used was simple random sampling. The data analysis was carried out by the ichi-square test which was then carried out by the logistic regression test.This research shown76.7% of students suffer from dyspepsia, 65%experience stress, 61.7% have irregular eating patterns and 40% of students consume irritating foodstuffs. Stress and regularity in eating patterns affected the incidence of dyspepsia (p=0.022 and p=0.006), while irritative foods had no effect on dyspepsia (p=0.998).Stress and regularity of eating patterns affect the incidence of dyspepsia.